PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PENGEMBANGAN SISTEM PENDUKUNG BAGI USAHA MIKRO KECIL MENENGAH (UMKM) KOTA MEDAN - Dilli Asril (Universitas Medan Area, 2014)
Micro, small and medium enterprises (SMEs) are the supportyng system of the economy of the people who are expected to become an integral part of the people economy. SMEs are also expected to overcome the obstacles that poverty. One of the participating office are implement eradication program is Dinas Koperasi dan UMKM Medan, in 2012 has implemented several programs supporting reduce poverty in the city of Medan. Type research descriptive and techniques of collecting data with an informer a lock (key informen) and a questionnaire to 50 people msmes picking up medan with uses the technique ball of snow. The results of research shows the existence of different activity that is performed dept. of cooperatives to develop msmes with convention of various seminars and training to increase knowledge and skill